The New Surface-Modified Flow Diverter p48 MW HPC Device Implanted in Arteries under 2.0 mm Diameter for Treatment of Distal Intracranial Aneurysms - Fernandes, Pedro Lucas Moreira; de Castro-Afonso, Luis H.; Nakiri, Guilherme Seizem; de Oliveira, Ricardo Santos; Colli, Benedicto Oscar; Abud, Daniel Giansante (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
Preliminary studies on the new modified surface flow diverters (FD) have shown promising results in the treatment of distal aneurysms. However, there is a lack of data in the literature regarding the use of these devices in very small-caliber arteries. The aim of this study was to analyze the safety and efficacy of the p48 MW HPC device (Wallaby-phenox, Bochum, Germany) device in the treatment of intracranial aneurysms associated with parent arteries with a diameter of <2.0 mm.Sixteen patients were prospectively evaluated from November 2019 to July 2023. All patients underwent follow-ups at 1, 6, and 12 months. Safety was assessed using the modified Rankin Scale and the National Institutes of Health Stroke Scale. Efficacy was defined as complete (grade D) or partial (grade C) aneurysm occlusion, as assessed by the O'Kelly–Marotta scale (OKM).The mean proximal and distal artery diameters were 1.61 mm (1.3–1.9) and 1.5 mm (1.0–1.8), respectively. All procedures were performed with technical success, and no severe adverse events occurred. At the 12-month follow-up, no patients experienced serious adverse events, new neurological symptoms, or deficits. At this stage, seven aneurysms were completely occluded (OKM grade D: 43.7%), and four aneurysms showed entry remnant contrast (OKM grade C: 25%).The treatment of distal unruptured aneurysms with the p48 MW HPC device device appears to be safe in vessels with a diameter of <2 mm. Larger studies with long-term follow-ups are necessary to better clarify the outcomes reported.
Keywords: flow diverter; distal intracranial aneurysms; small vessels